Unruptured ectopic pregnancy in rudimentary horn of unicornuate uterus at fourteen weeks with previous vaginal delivery - Hindocha, Jaydip; Sonaiya, Sneh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Unicornuate uterus with a rudimentary horn is an anomaly of the mullerian duct and is an extremely rare condition. This condition results when one of the paired mullerian ducts fails to fuse completely. Its incidence is estimated to be one in 76,000 pregnancies.Pregnancy in the rudimentary horn of the unicornuate uterus is difficult to diagnose on ultrasound and can be easily missed out. Hence the pregnancy usually gets detected after rupture when the mother presents with the complaint of severe abdominal pain. This is a case report of a 24 year old G2P1A0L1 female who presented to us with complaints of tenderness in the left iliac fossa and mild abdominal distention. Clinical examinations, radiological investigations, and exploratory laparotomy revealed a unicornuate uterus with an unruptured left rudimentary horn pregnancy at 14 weeks with mild hemoperitoneum. Following the exploratory laparotomy, excision of the left rudimentary horn and thorough peritoneal lavage was performed.